I-physio profile designer concept: How to avoid conventional impression - Legros J. Michel; Michel J.F (DiscoverSys Inc., 2019)
Objective: Present a new technique réduction the clinical steps of implant placement and impression for crown on implant. Develop the concept of gingival sculpting with I-physio healing abutments.Methods:This case presentation shows how to use the new concept of I-physio profile designer abutment to shape the gingiva during healing and use this abutment for impression before placing the final crown.Results: This simplified procedure shows that I-physio profile designer abutments reduce the clinical and prosthetic steps in implantology.Conclusion: In the future, implantology and prosthodontics on implants will certainly benefit from this technique and improve the long-term results for the patients.